Assessment of Infection Control Process at Hemodialysis Units in Kurdistan Region - Khalida A.M.Al-Gersha (Iraqi National Journal of Nursing Specialties, 2023)
Objective: to assess the infection control process in hemodialysis units and to find out the relation shipbetween nurses practices and some of the demographic characteristics.Methodology:٨descriptive study was conducted at hemodialysis units in Hawler hospital and Azadhospital in Duhok Governorate, from 15th of January2004 to the end of May 2005Non-probability Sampling was performed, a purposive sample of (40) Nurses who worked inhemodialysis units, a purposive sample of (63) patients who were attending to the hemodialysis unit attime of the data collection ,and taking swab from different site of vascular access (fistula, shunt).٨checklist was constructed by investigator in regard to the purpose of the present study which includedthe different tools were used through the data collection.part one: -٨ checklist for environmental precaution concerning infection control.Part two: A-questioner for Sociodemographic characteristic for nurses. B - observational checklistform for nursing practice concerning infection Control.Part three: -٨ questioner for socio and clinical demographic of ([559) patient B- patient practiceconcerning infection Control.Part four: Swab specimens were also gathered from vascular access site. Content validity of thechecklist was responses through panel of (16) experts. Reliability of checklist was determined throughuse of inter-observer questionnaire for nursing practice and the test- retest for patient practice.Results: The results of the study revealed that the presents of isolate room at hemodialsis unit forpatients with HBV. The result also revealed that the standard precaution that was applied in dialysisunit concerning infection control was adequate application of standard precaution of ventilation with٠College of Nursing/ University of Irbil٠٠ Adult Nursing Department /College of NursingاUniversity of Baghdad74Infection Control Process at Hemodialysis Unitsgrand mean of Score (2.00), sterilization of the dialysis machine, and walls and floor cleaning withgrand mean of score (1.85). The data analysis indicated that the majority of nurses were male, with agegroup (21-30) years. And more than half of them graduated from institute. The result also indicated(82.5%) of nurses had (1-3) years of experience in hemodialysis (95%) had no training session aftergraduation.Concerning nurse's practice, the data revealed inadequate practices related to cleaning patient’sbed and linens management, fistula care and instrument preparation, isolation room, sharp equipmentmanagement, drugs administration management and instruction. Significant differences were foundbetween nurse’s practices and place of work, and no significant differences were found betweennurse’s practice concerning infection control and certain variables such as sex, age, marital status, levelof education and years of experience in hemodialysis and peritoneal dialysis.The result shows that the half of patients of dialysis were male, their age ranged between (51-60)years and had (1-5) years history of renal failure. Regarding patient practice, the patient had high meanofscore for doing laboratory tests.Recommendation: The study recommended that the periodic evaluation for the environmental nurse’spractices concerning infection control at dialysis unit and continuous training and education should beconducted for all the nursing staff.